2006
DOI: 10.4088/jcp.v67n0503
|View full text |Cite
|
Sign up to set email alerts
|

The Brown Longitudinal Obsessive Compulsive Study

Abstract: The demographics, clinical characteristics, comorbidity rates, and symptom presentation of the sample are consistent with those reported for cross-sectional studies of OCD, including the DSM-IV Field Trial. The current sample has a number of advantages over previously collected prospective samples of OCD in that it is large, diagnostically well characterized, recruited from multiple settings, and treatment seeking. This unique data set will contribute to the identification of meaningful phenotypes in OCD based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
97
1
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 333 publications
(107 citation statements)
references
References 43 publications
7
97
1
2
Order By: Relevance
“…In women, the prevalence of eating disorders was increased (26% of the sample). Data from the Brown cohort 68 showed that a minority of patients (< 10%) had not experienced any other disorder in their life. As reported elsewhere, depression was the most common comorbid condition (67% lifetime prevalence and 15% current episode).…”
Section: Aetiologymentioning
confidence: 99%
“…In women, the prevalence of eating disorders was increased (26% of the sample). Data from the Brown cohort 68 showed that a minority of patients (< 10%) had not experienced any other disorder in their life. As reported elsewhere, depression was the most common comorbid condition (67% lifetime prevalence and 15% current episode).…”
Section: Aetiologymentioning
confidence: 99%
“…Indication for this hypothesis comes from studies that utilized structured interviews and DSM-IV criteria demonstrating cooccurrence rates that range between 23 and 45 % [21,49,[52][53][54]. Lower co-occurrence rates were found in (earlier) studies in which DSM-III, DSM-III-R or ICD-10-criteria were utilized as well as clinical judgments, questionnaires, and semistructured interviews for diagnostic assessment purposes [e.g.…”
Section: Ocpd and Obsessive-compulsive Disordermentioning
confidence: 99%
“…Further evidence for an overlap between OCD and OCPD originates from studies showing significantly higher cooccurrence rates between OCPD and OCD than between OCPD and the general population [21,22] or other mental disorders [52,58] (for contradictory findings, see Albert et al, 2004 [21]) (for more details, see Table 1). Even more evidence comes from studies demonstrating (significantly) higher comorbidity rates between OCPD and OCD than between other personality disorders and OCD [22,53,54,56,59,60]. Moreover, studies investigating similarities and differences between both disorders specified that (pure) obsessions as well as contamination and cleaning-related symptoms seem to be specific for individuals with OCD, whilst rigidity and excessive self-control were found to be specific for individuals with OCPD [8•, 48].…”
Section: Ocpd and Obsessive-compulsive Disordermentioning
confidence: 99%
“…The resulting consequences reflect in the long delay from the onset of the disorder until the first treatment, on average 11 years [19]. Thus, there is a demand for new developments in the psychotherapeutic care of OCD.…”
mentioning
confidence: 99%